2022
DOI: 10.1155/2022/3181427
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Network Meta-Analysis about the Efficacy and Safety of Tripterygium wilfordii Hook F in Rheumatoid Arthritis

Abstract: Objective. This study aims to evaluate the efficacy of various conventional synthetic DMARDs, including Tripterygium wilfordii Hook F (TwHF) for treating rheumatoid arthritis (RA) by network meta-analysis. Methods. We retrieved the related literature from online databases and supplemented it by using a manual retrieval method. Data was extracted from the literature and analyzed with STATA software. Results. A total of 21 trials (5,039 participants) were identified. Assessment of ACR20 response found that TwHF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Tripterygium wilfordii Hook.f., also called Leigongteng in TCM, is a commonly used anti-rheumatic herbal drug [ 137 ]. Triptolide (TPL) is a diterpene lactone epoxide compound extracted from Tripterygium , and it possesses diverse biological profiles, such as anti-fertility, anti-tumour, anti-inflammatory, as well as immunosuppressive activities [ 138 , 139 ].…”
Section: Cerna Involved In Tcm Treatment Of Ramentioning
confidence: 99%
“…Tripterygium wilfordii Hook.f., also called Leigongteng in TCM, is a commonly used anti-rheumatic herbal drug [ 137 ]. Triptolide (TPL) is a diterpene lactone epoxide compound extracted from Tripterygium , and it possesses diverse biological profiles, such as anti-fertility, anti-tumour, anti-inflammatory, as well as immunosuppressive activities [ 138 , 139 ].…”
Section: Cerna Involved In Tcm Treatment Of Ramentioning
confidence: 99%
“…Similarly, a further systematic review and network meta-analysis evaluating the efficacy and safety of T. wilfordii in treating RA found that the glycosides of this plant administered in combination with MTX may have been the optimal treatment of choice based on an assessment of the ACR20 response. Moreover, among the different treatments assessed, the use of T. wilfordii glycosides alone ranked second only to the T. wilfordii glycoside + MTX combined treatment (Wang et al, 2022).…”
Section: Tripterygium Wilfordii In the Treatment Of Ramentioning
confidence: 99%
“…More randomized clinical trials of better quality have been published, showing beneficial effects of herbal medications in conditions such as diabetes mellitus 47 , hypertension 48 , reduction in proteinuria and renal function decline [49][50][51] . A number of meta-analyses published in recent years evaluated the effects of herbal medicine in different medical conditions, including bronchiolitis in infants 52 , psoriasis 53 , rheumatoid arthritis 54 , and irritable bowel syndrome 55 . While the herbal medicines appear to be safe, the available evidence in the literature does not appear to be sufficient or vigorous enough to confirm their benefits 53,55 .…”
Section: The Science Of Herbal Medicinesmentioning
confidence: 99%